Comprehensive Safety Requirements for Thermal Insulation Works of Structure of the Building - Azamatovich, Khabibullaev Shavkat (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes the complex requirements for the creation of safe working conditions during thermal insulation of building envelopes.